2020
DOI: 10.1111/jpim.12545
|View full text |Cite
|
Sign up to set email alerts
|

Big Data for Creating and Capturing Value in the Digitalized Environment: Unpacking the Effects of Volume, Variety, and Veracity on Firm Performance*

Abstract: Despite significant academic and managerial interest in big data, there is a dearth of research on how big data impacts the long‐term firm performance. Reasons for this gap include a lack of objective indices to measure big data availability and its impact, and the tendency of studies to ignore the costs associated with collecting and analyzing big data, assuming that big data automatically delivers benefits to firms. Focusing on how firms create and capture value from big data about customers, we use the reso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
184
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 232 publications
(190 citation statements)
references
References 106 publications
(209 reference statements)
2
184
0
4
Order By: Relevance
“…At this level of analysis, Cappa et al (this issue) study how the characteristics of big data (volume, variety, and veracity) affect long‐term firm performance, hence contributing to a better theoretical understanding of the opportunities and challenges going along with the adoption of these new technologies. In particular, the authors conduct an empirical analysis on a sample of downloads of mobile device applications and find that volume of big data harms firm performance, while variety moderates this negative relationship.…”
Section: Framing and Discussing The Papers Included In The Special Issuementioning
confidence: 99%
See 1 more Smart Citation
“…At this level of analysis, Cappa et al (this issue) study how the characteristics of big data (volume, variety, and veracity) affect long‐term firm performance, hence contributing to a better theoretical understanding of the opportunities and challenges going along with the adoption of these new technologies. In particular, the authors conduct an empirical analysis on a sample of downloads of mobile device applications and find that volume of big data harms firm performance, while variety moderates this negative relationship.…”
Section: Framing and Discussing The Papers Included In The Special Issuementioning
confidence: 99%
“…The papers published in this special issue discuss and analyze some of these under‐investigated issues. Specifically, by covering three level of analysis (namely, macro, meso, and micro), and by integrating both qualitative and quantitative research methodologies, they shed new light on digital product platforms (Hilbolling et al, this issue), provide evidence about the impact of big data on firm performance (Cappa et al, this issue), investigate the role of organizational adaptability, agility, and ambidexterity on digital trasnformation (Scuotto et al, this issue), frame the influence of digitization and connectivity on knowledge search and recombination (Lanzolla et al, this issue), analyse the role of digital machines on production process routines (Aversa et al, this issue), discuss how the interplay between family management and technological diversification shape the development of exploratory and exploitative IoT innovations (Ceipek et al, this issue), unveil how employees respond to ambidextrous organizational models to accelerate digital innovations (Smith & Beretta, this issue), assess the impact of digital tools on organizational practices in the innovation process (Marion & Fixson, this issue).…”
Section: Introductionmentioning
confidence: 99%
“…Big data means such volumes of information collected from various sources, where processing using traditional methods becomes very difficult or impossible [2,3]. At the same time, most researchers agree that big data can be understood through not only the volume, but also their ability to be sources for generating valuable information and ideas [4].…”
Section: Introductionmentioning
confidence: 99%
“…More importantly, it has been reported that people's personal data is just that personal; when an organization fails to protect it from loss, damage or theft, it is more than an inconvenience [3]. Another concern is when a firm's digitalization practices are deemed improper distribution and use of customer data [4]. Moreover, bankruptcy happened, due to a data breach [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Another concern is when a firm's digitalization practices are deemed improper distribution and use of customer data [4]. Moreover, bankruptcy happened, due to a data breach [4,5].…”
Section: Introductionmentioning
confidence: 99%